Simulation of the interaction of 4 rotors of a quadcopter in hover (2017)
Quadcopters are the main platform for Unmanned Aerial Vehicle (UAV), the use of this technology is growing fast for different industries as agriculture, mining and oil and gas. The understanding of the aerodynamics of UAVs in especially of their propulsion system have become an important field of research in recent years. In the present study, a Computational Fluid Dynamics (CFD) model is implemented in order to simulate the dynamics of the flow (in hover condition) around the 4 propellers typically used in commercial quadcopters. The model was to simulate the interaction of the wake of the four rotors using symmetric boundary conditions. Numerical results show the capabilities of the CFD model to predict lift and torque coefficients of the propeller. For validation, numerical results of thrust and torque were compared to experimental measurements of flying test and with a model in which only one rotor was implemented. The wake, forces...